2021
DOI: 10.1002/jum.15766
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya Fever: Comparison Study of Synovitis and Tenosynovitis of the Hands and Wrists Using Physical Examination, Ultrasound, and MRI Findings

Abstract: Objectives To compare musculoskeletal changes on a physical examination (PE), ultrasound (US) and magnetic resonance imaging (MRI) of the hands and wrists of patients with Chikungunya fever (CF). Methods The sample consisted of 30 patients in the chronic phase of CF. The sites analyzed were the interphalangeal (IP), metacarpophalangeal (MCP) and wrist/mediocarpal (WMC) joints and periarticular soft tissue. The interval between the PE and imaging tests was 7 days, and the interval between US and MRI was 2 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Similarly, in another study that evaluated hands and wrists of 50 patients with chronic musculoskeletal symptoms secondary to CHIKF in Brazil, synovitis was the most common finding (84.0%) [ 35 ]. Furthermore, a recent study confirmed that US could be of great value in confirming clinical findings in CHIKF patients, with the advantage of being a non-invasive, low-costing, and accessible exam [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in another study that evaluated hands and wrists of 50 patients with chronic musculoskeletal symptoms secondary to CHIKF in Brazil, synovitis was the most common finding (84.0%) [ 35 ]. Furthermore, a recent study confirmed that US could be of great value in confirming clinical findings in CHIKF patients, with the advantage of being a non-invasive, low-costing, and accessible exam [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nine patients had normal baseline radiographs, but MRI revealed erosions in the hands of five of the six patients with normal radiographs. Leidersnaider et al 21 examined joint involvement in 30 patients (26 women) with CCA with ages ranging from 32 to 73 years (mean age 54.7 ± 10.0 years) using physical examination, ultrasonography, and MRI. The mean time from diagnosis to ultrasonography was 336.1 ± 251.7 days, ranging from 53 to 911 days, and the mean time from diagnosis to MRI was 337.5 ± 251.7 days, ranging from 54 to 913 days.…”
Section: • Study Findingsmentioning
confidence: 99%